Research Progress on the Clinical Application and Mechanisms of the Five Shu Points - Ji, Yingjie; Sa, Yuping (Journal of Contemporary Medical Practice, 2025)
The Five Shu Points, as specific acupoints in acupuncture meridian theory, have a wide range of clinical applications. By reviewing domestic research literature on the clinical use and mechanisms of action of the Five Shu Points from 2020 to 2025, it has been found that their therapeutic effects are mainly exerted through the following mechanisms: 1) Regulation of programmed cell death; 2) Intervention in inflammation; 3) Neuroprotective function. These findings not only provide a scientific basis for the clinical application of the Five Shu Points but also offer new directions for future research on the mechanisms and expanded application of acupuncture treatment. They promote the modern interpretation and precise application of acupuncture theory.